In Search of a Cultural Republic: Intellectual and Literary Periodical Publishing in Dublin 1930-55 - Perkins, Sonya (Trinity College Dublin, School of Histories & Humanities, History Department, 2019)
The subject of this thesis is intellectual and literary periodical publishing in Dublin from 1930 to 1955. Close analysis has focused on The Capuchin Annual, The Dublin Magazine, Motley, Ireland To-Day, Commentary, The Bell and Envoy, but these periodicals have been contextualized among their peers, and those periodicals, too, have been woven into this thesis. This thesis provides a nuanced historical study of these intellectual and literary periodicals by locating them within the broader cultural history and publishing landscape, by providing a comparative analysis of their content, operating models and peers, and by considering the convergence of culture and commerce within their pages. These periodicals complicate the picture of post-independence Ireland as a closed-off culture, both in terms of the platform that they provided for new ideas and debates but also in terms of how the editors of these periodicals marketed them among an international network of intellectual periodicals. This thesis considers the fluidity of intellectual and literary publishing and the overlapping spheres of influence - cultural and commercial - in Dublin during the period under review. This thesis argues that writers moved more fluidly between markedly different periodicals such as the traditional Capuchin Annual and the modernist Bell than has previously been acknowledged. These periodicals were commercial operations as well as cultural projects, and the business operation of these periodicals is interrogated to unravel the various revenue streams that made publication possible. It addresses the fundamental question of how these intellectual and literary periodicals operated financially in a publishing market that was flooded by British imports and in an era before the Arts Act and the belated State acknowledgement of its role to promote knowledge and appreciation of the Arts.
Keywords: Periodicals; Publishing; Ireland